A hospital based follow up study on predictors of mortality in patients with Intra cranial hemorrhage - Kishan, U.; B., Rajiv Kumar; N., Arun Kumar (International Journal of Advances in Medicine, 2018)
Background: Intra-cerebral hemorrhages account for approximately 10-15 percent of all stroke cases and are associated with the highest mortality rate (30-40%). Study of predictors can modify the mortality rates. The objective of the present study the predictors of mortality in patients with intra cranial hemorrhage. Methods: Hospital based cross sectional study was carried out. Forty patients with CT scan evidence of intra cranial hemorrhage admitted to our hospital were randomly selected. All investigations were done. Patient characteristics were noted down. Results: In the present study among 40 patients, 16 patients died. The mortality was 40%. As the age increased, the mortality rate increased. But there was no difference between the mortality among males and females. Mortality was more than twice among those with SBP more than 180 mmHg i.e. 58.8% compared to only 26.1% among those with SBP less than 180 mmHg. Similar findings were noted for DBP and MAP. As the severity of motor weakness increased, the mortality increased. Patients with presence of bilateral plantar extensor response were found to be more at risk of death with a death rate of 66.7% compared to only 18.2% among those without presence of bilateral plantar extensor response. As the Glasgow coma scale increased, the mortality decreased from 100% in patients with a score of 3-4 to only 31.2% in patients with a score of 9-13. Intra-ventricular extension of haemorrhage, presence of hydrocephalus, volume of hematoma >30 ml, decreased consciousness level was important predictors. Conclusions: Bad prognosis i.e. death can be expected if the patient is older, low GCS, hematoma size > 30 ml, gaze palsy, severe motor neuron weakness, abnormal pupils, ataxic respiration etc. hence intensive care should be given to such patients to bring down the mortality.